Correlation of Tumor Marker Cancer Antigen (CA-125) against Hemoglobin, Leucocytes, and Platelet Lymphocyte Ratio in Ovarian Cancer Patients at RSUD ULIN Banjarmasin - sabarudin, hermin (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
CA-125 is the most commonly used tumor marker in ovarian cancer, its known as the "Gold Standard" for the diagnosis of ovarian cancer. CA-125 allegely related to the inflammatory mechanisms which associated with leukocytes and lymphocytes, as well as Lymphocyte Platelet Ratio. This study is to prove above hypothesis. The objective is to investigate CA-125 correlation as tumor marker of inflammatory hematology examination which consisting of Hemoglobin, leucocytes and PLR as indicator of inflammatory examination in ovarian cancer patient. The method is an observational analytic study with cross sectional retrospective descriptive. The sample is 42 patients medical record who are treated in Oncology Polyclinic RSUD ULIN in October 2014 - October 2017 period. Samples selected by time limitation method. Sampling technique using nonpropability method followed by purposive sampling method. After the data is taken and selected then processed into SPSS for normality test and continued by multiple linear regression test. The results showed that correlation analysis of CA-125 tumor marker on Hb, leukocyte and PLR levels was P = 858b; P value <0.05. The CA-125 relationship to Hb, leucocytes and PLR is a negative relationship (r Hb = -3,463, r leukocytes = -6,117, r PLR = -2.281), which means that more high the Hb, leukocyte and PLR value, conversely CA125 value become more low. The conclusions of this study is there no correlation of CA125 tumor marker against Hb, leucocytes and PLR in ovarian cancer patients. The results of this study indicate that the increasing of CA125 value is negative correlation because it is not followed by decreasing of Hb, increasing of leukocyte and PLR.Â